Genetic diversity analysis of released Indian linseed (Linum usitatissimum L.) varieties using SSR markers: Genetic diversity analysis of released Indian linseed (Linum usitatissimum L.) varieties using SSR markers - HELAN BABY THOMAS,; A DIVYA,; A L RATHNAKUMAR,; M SUJATHA, (Journal of Oilseeds Research, 2023)
A genetic diversity analysis was performed on 91 released linseed varieties of India using 20 polymorphic linseed specific SSR markers. The genotypes were categorized in to 15 clusters. The mean allele frequency was 0.7 and Shannon diversity index was 4.15, indicating that the germplasm was highly diverse.